Failure analysis of thin-walled composite profiles subjected to axial compression using progressive failure analysis (PFA) and cohesive zone model (CZM) - Rozylo, P.; Wysmulski, P. (Composite structures, 2021)
In the presented paper, the phenomenon of failure of axially compressed thin-walled composite structures with channel shape was analysed. The tested thin-walled structures were made of CFRP composite using the autoclave method. In the research, experimental tests on actual columns and advanced numerical calculations using the finite element method were conducted. The numerical calculations were carried out in the ABAQUS® software. The axial compression tests of thin-walled structures made of composite materials were conducted in the full load range, taking into account the failure phenomenon. During the experimental tests, post-critical equilibrium paths were recorded with the simultaneous recording of acoustic emission signals. This approach made it possible to carry out further analysis of the failure of the composite material. Numerical simulations were conducted using progressive failure analysis (PFA), based on the damage initiation (Hashin’s criterion) and the damage evolution (energy criterion). Additionally, the cohesive zone model (CZM) was used in numerical studies. A measurable effect of the conducted numerical research was the analysis of the failure phenomenon in the context of progressive failure analysis (PFA) and the delamination phenomenon accompanying the loss of load capacity (CZM), which was the main novelty in relation to the current works in the literature on the subject. The obtained results of the numerical tests showed a high compliance with the results of the experimental studies.